The Level of Applying Electronic Administration at Yarmouk University as Percived by Administrators and Faculty Members - Abu-Ashour, Khalifeh; Al-Nimty, Deana (Jordan Journal of Educational Sciences, 2013)
The purpose of this study was to reveal the level of applying electronic administration at Yarmouk University. The study population consisted of all faculty and administrative members at the university (N=2410), of which (683) are faculty members, and (1727) are administrators during the academic year 2010/2011. The sample of the study consisted of (647) faculty and administrator members of which (320) faculty members, and (327) administrators, who were selected randomly from the study population. To achieve the objectives of the study the researcher prepared a questionnaire that included (55) items distributed among four ranks. The results of the study showed that the level of applying electronic administration from the perspectives of faculty members was high, and the electronic execution rank placed first with a high degree, while the electronic supervision and evaluation rank placed last with a moderate degree. The results also showed that the level of applying electronic administration from the perspectives of administrators was moderate, and the electronic execution rank placed first with a high degree, while the electronic planning placed last with a moderate degree. The results indicated that there were no significant differences in the perspectives of faculty members regarding the level of applying electronic administration according to the study variables such as academic level, gender, and college among all ranks. The results, however, indicated that there were no statistical significant differences in the perspectives of administrators related to the level of applying electronic administration due to the difference of gender among all ranks, and there were statistical significant differences according to the difference of academic qualification variables between the holders of Diploma or less, and the Bachelor and the graduate studies in the electronic planning and electronic supervision and evaluation on all ranks. Additionally, there were differences between the holders of Diploma or less and the Graduate Studies in favor of graduate studies related to electronic execution rank.